2010
DOI: 10.1523/jneurosci.5825-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Amyloid β Oligomers: Their Contribution to Synaptic Alteration, Abnormal Tau Phosphorylation, Glial Activation, and Neuronal LossIn Vivo

Abstract: Although amyloid ␤ (A␤) oligomers are presumed to cause synaptic and cognitive dysfunction in Alzheimer's disease (AD), their contribution to other pathological features of AD remains unclear. To address the latter, we generated APP transgenic mice expressing the E693⌬ mutation, which causes AD by enhanced A␤ oligomerization without fibrillization. The mice displayed age-dependent accumulation of intraneuronal A␤ oligomers from 8 months but no extracellular amyloid deposits even at 24 months. Hippocampal synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
367
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(392 citation statements)
references
References 51 publications
21
367
0
Order By: Relevance
“…6B). Importantly, these same pathways involving phospho-tau and caspase-3 previously were shown to be involved in oligomeric Aβ-induced abnormal excitability and synaptic spine loss (10,11,14,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). For example, the relatively specific inhibitor of caspase-3 activity, z-DEVD-fmk, blocks a pathway leading to dendritic spine shrinkage via activation of calcineurin, which results in dephosphorylation and internalization of synaptic AMPARs (56).…”
Section: Extrasynaptic Nmdars Mediate Aβ-induced Molecular Cascadesmentioning
confidence: 85%
“…6B). Importantly, these same pathways involving phospho-tau and caspase-3 previously were shown to be involved in oligomeric Aβ-induced abnormal excitability and synaptic spine loss (10,11,14,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). For example, the relatively specific inhibitor of caspase-3 activity, z-DEVD-fmk, blocks a pathway leading to dendritic spine shrinkage via activation of calcineurin, which results in dephosphorylation and internalization of synaptic AMPARs (56).…”
Section: Extrasynaptic Nmdars Mediate Aβ-induced Molecular Cascadesmentioning
confidence: 85%
“…Neuronal loss and atrophy are one of the hallmarks of and cause of memory deficits in AD in humans. 23,24 Recent studies showed that Ab-binding heat-shock proteins, which prevent Ab aggregation and oligomerization, inhibit Ab-induced neuronal death. 19,25 To elucidate the effect of DBP on the cytotoxicity of Ab, we examined whether DBP influences Ab-mediated neuronal death using the MTT assay, MTS assay, and DAPI staining.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to short-term effects, oligomers have been shown to impair synaptic plasticity by blocking longterm potentiation and reinforcing long-term depression (72). Tomiyama et al (73) generated APP transgenic mice expressing the E693⌬ mutation, which causes neuronal cell death and cognitive impairment by enhanced intracellular A␤ oligomerization without plaque formation.…”
Section: Soluble Oligomeric Pyroglutamate A␤: the Missing Link In A␤mentioning
confidence: 99%